PENGARUH MINAT DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR BAHASA JEPANG SISWA KELAS XI SMK KANSAI PEKANBARU - Tiara Maulani; Hana Nimashita; Dini Budiani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2026)
Abstract: This study aims to examine whether learning interest (X₁) and learning motivation (X₂) have an effect on Japanese language learning achievement (Y) among class XI students at SMK Kansai Pekanbaru in the 2025/2026 academic year. A descriptive quantitative method with multiple linear regression analysis was used. The total population was 91 class XI students studying Japanese, and 44 students were selected as the sample using quota sampling based on high, medium, and low levels of interest and motivation. Data were collected through a 4-point Likert scale questionnaire that had been tested for validity and reliability using IBM SPSS Statistics 25. The results show that: (1) learning interest had no significant effect on learning achievement (t = 0.982 t-table = 2.080; sig. 0.332 0.05; R² = 0.022); (2) learning motivation also had no significant effect (t = 0.258 t-table = 2.080; sig. 0.789 0.05; R² = 0.002); (3) when both variables were tested simultaneously, they still showed no significant effect (F = 0.919 F-table = 3.226; sig. 0.407 0.05; R² = 0.043). This means that 95.7% of the variation in student achievement is explained by other factors, such as cognitive ability, teaching quality, and learning environment.